Effect of the cement-rice husk ash on the plasticity and compaction of soil - Basha, E.A.; Hashim, Roslan; Muntohar, A.S. (2003)
The chemical stabilisation of soils was studied by using cement and rice husk ash. Three types of soils, residual soils, kaolinite and bentonite, were used in the study. The experimental study included the evaluation of the main index properties of the soil and compaction, along with a characterisation of the materials through X-Ray diffraction. Test results show that both cement and rice husk ash reduces the plasticity of soils. In term of compactability, addition of rice husk ash and cement decreases the maximum dry density and increases the optimum moisture content. From the viewpoint of plasticity, compaction characteristics, and economy, addition of 6 - 8 percent cement and 10 - 15 percent rice husk ash are recommended as an optimum amount.